Bioavailability of Tryptophan Biomass for Laying Hens - Stéphane Cristyne O. Estevão; Gabriel Henrique Nacamura da Silva; Livia Rastoldo R. Oliveira; Larissa Oliveira dos Santos; Erikson Kadoshe M. Raimundo; Rita Brito Vieira; Tiago A. Rodrigues; Bernardo Rocha F. Nogueira; Eliane Aparecida da Silva; Lizandra Amoroso; Michele Bernardino de Lima; Edney Pereira da Silva (Animals)
Two concurrent assays were conducted with the objective of evaluating the bioequivalence and determining the relative bioavailability value (RBV) of L-tryptophan biomass 60% for laying hens. In both assays, L-tryptophan 98% was used as the reference source. A total of 216 hens were used in the two assays. The first assay was performed using the direct comparison method to assess bioequivalence between the sources. In the second assay, the slope ratio method was used to determine the RBV. The variables analyzed were feed intake, tryptophan intake, egg production, egg weight, daily egg mass, feed conversion ratio, feed efficiency, yolk weight, shell weight, albumen weight, albumen height, eggshell thickness, Haugh unit, body protein weight, body lipid weight, body water weight, and body ash weight. The data from both assays were submitted to analysis of variance, and we only applied linear regression to variables from the data obtained using the slope ratio method that were significant at 0.05. The results obtained via the direct comparison method showed no significant difference (p > 0.05) between the L-tryptophan sources when using ANOVA. In the slope ratio method, the treatments only affected the egg production and daily tryptophan intake responses of the hens and linear equations were adjusted. No differences (p > 0.05) were found for egg quality. When we applied the slope ratio in adjusted equations, we found that the RBV = 100%. The results showed that the utilization of L-tryptophan biomass 60% in the diet of laying hens was bioequivalent.